Respuesta :

Use Negative Power Rule: {x}^{-a}=\frac{1}{{x}^{a}}x−a​​=x​a​​​1​​
\frac{1}{{6}^{2}}6​2​​​1​​
2 Simplify {6}^{2}6​2​​ to 3636
\frac{1}{36}36​1​​
Done

Decimal Form: 0.027778

Answer:

[tex]\frac{1}{36}[/tex]

Step-by-step explanation:

The given expression is [tex]6^{-2}[/tex]

We can use the exponent property to simplify this expression.

Rule: [tex]x^{-a}=\frac{1}{x^a}[/tex]

Applying this rule, we get

[tex]6^{-2}\\\\=\frac{1}{6^2}[/tex]

On simplifying the denominator

[tex]\frac{1}{6^2}\\\\=\frac{1}{36}[/tex]

Therefore, the simplified expression is [tex]\frac{1}{36}[/tex]